2019
DOI: 10.3390/ijms20061301
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Vitamin D Supplementation in the Management of Multiple Sclerosis: A Systematic Review

Abstract: Objective: to examine the extent of effect vitamin D in Multiple Sclerosis (MS) on pathology and symptoms. Methods: A literature search was performed in November 2018 (CRD42018103615). Eligibility criteria: randomised control trials in English from 2012 to 2018; a clinical diagnosis of MS; interventions containing vitamin D supplementation (vitamin D3 or calcitriol) in disease activity compared to a control/placebo; improvement in: serum 25(OH)D, relapse rates, disability status by Expanded Disability Status S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 30 publications
0
30
1
3
Order By: Relevance
“…To address these shortcomings, systematic reviews have been undertaken to examine the effect of vitamin D supplementation on MS; however, some of these have been limited by lack of a range of vitamin D status and not accounting for bias [167] or failure to assess cytokine outcomes or baseline vitamin D on outcomes [168]. A third systematic review has attempted to address some of these former weaknesses [169]. In this meta-analysis which included 10 studies, vitamin D supplementation was compared to placebo or low dose vitamin D. Overall, disease measures improved to a greater extent in patients with lower baseline serum 25(OH)D levels.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…To address these shortcomings, systematic reviews have been undertaken to examine the effect of vitamin D supplementation on MS; however, some of these have been limited by lack of a range of vitamin D status and not accounting for bias [167] or failure to assess cytokine outcomes or baseline vitamin D on outcomes [168]. A third systematic review has attempted to address some of these former weaknesses [169]. In this meta-analysis which included 10 studies, vitamin D supplementation was compared to placebo or low dose vitamin D. Overall, disease measures improved to a greater extent in patients with lower baseline serum 25(OH)D levels.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Overall, 11 records were included in this review [100,[204][205][206][207][208][209][210][211][212][213] (Supplemental Figure S6). We focused on publications that examined the association between vitamin D and the development of MS or clinical activity of MS. Supplemental Tables S22-S24 provide information about the included studies and the assessed quality based on AMSTAR 2.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding clinical outcomes, eight publications that conducted SRs of mainly RCTs [204,205,207,[209][210][211][212][213] focused on changes in the expanded disability status scale (EDSS). In summary, the studies found no significant therapeutic effect of vitamin D on EDSS and/or concluded that vitamin D supplementation had no effects on EDSS.…”
Section: Therapeutic or Adjuvant Vitamin D Supplementation In Ms Patimentioning
confidence: 99%
See 2 more Smart Citations